dXNP/DATRX increases apoptosis via the JNK and dFOXO pathway in Drosophila neurons. - Hong, Y.K.; Lee, N.G.; Lee, M.J.; Park, M.S.; Choi, G.; Suh, Y.S.; Han, S.Y.; Hwang, S.; Jeong, G.; Cho, K.S. (Biochemical and Biophysical Research Communications, 2009)
Mutation of the XNP/ATRX gene, which encodes an SNF2 family ATPase/helicase protein, leads to ATR-X syndrome and several other X-linked mental retardation syndromes. Although XNP/ATRX is a chromatin remodeler, the molecular mechanism by which mental retardation occurs in patients with ATR-X has yet to be determined. To better understand the role of XNP/ATRX in neuronal development, we expressed Drosophila XNP (dXNP/DATRX) ectopically in Drosophila neurons. Neuronal expression of dXNP/DATRX resulted in various developmental defects and induced strong apoptosis. These defects and apoptosis were suppressed by Drosophila inhibitor of apoptosis protein 1. Expression of dXNP/DATRX also increased JNK activity and the levels of reaper and hid transcripts, which are pro-apoptotic factors that activate caspase. Furthermore, dXNP/DATRX-induced rough eye phenotype and apoptosis were suppressed by dFOXO deficiency. These results suggest that dXNP/DATRX is involved in caspase-dependent apoptosis in Drosophila neurons via regulation of the JNK and dFOXO pathway.